ANALYSIS OF MARKETING PERFORMANCE OF THE PRODUCT PROGRAM OF INDEPENDENCE DEVELOPMENT IN CLASS IIA WOMEN'S PRIVATE VOCATIONAL SCHOOL, BANDUNG - Lauditta Indahdewi; Sri Sulistijaningsih (Polteknik Ilmu Pemasyarakatan, 2019)
The program of skill development and job training and production are one of the developing self-reliance that is carried out at the Lembaga Pemasyarakatan. This activity not only aims to develop the potential, talents and interest that the prisoners have, it also becomes a source of income for the prisoner during their criminal period. Prisoners who carry out this program are entitled to get premi as wages from the sale of the product. Therefore the higher the sales value, the more income will be obtained. In increasing sales, it is also necessary to do the right marketing strategy in order to increase consumer interest in providing products. Marketing performance is determined by environmental factors, product innovation, and marketing strategy creativity. This research focuses on looking at the implementation of skills development, analysis of environmental factors and the level of marketing performance in the Lapas Perempuan Kelas IIA Bandung. Data analysis techniques were carried out by descriptive method with a qualitative approach. The conclusion of this study is that there are still many constraints on environmental factors in Lapas Perempuan Class IIA Bandung that making other factors, namely product innovation, marketing strategy creativity and marketing performance hampered.